Characterization of a new BRCA1 rearrangement in an Italian woman with hereditary breast and ovarian cancer syndrome - Concolino, Paola; Rizza, Roberta; Hackmann, Karl; Paris, Ida; Minucci, Angelo; De Paolis, Elisa; Scambia, Giovanni; Zuppi, Cecilia; Schröck, Evelin; Capoluongo, Ettore (Breast cancer research and treatment, 2017)
We report a novel BRCA1 LGR, involving the complete duplication of exon 3, in an Italian patient with a strong family history of breast and ovarian cancer. Our purpose is to provide an effective characterization of this LGR using a combination of different methods able to establish the exact breakpoints of the duplication.